(untitled) (Bangladesh Journal of Psychiatry, 2024)
Suicide in schizophrenia is a major risk of premature death. Ketamine has been frequently shown to have immediate antidepressant effect and has a significant role to prevent suicidal attempt and plan in unipolar and bipolar depression. Though use of ketamine in severe depression with psychosis has been proven but the use in psychotic diseases has been generally ignored due to the risk of exacerbating dissociative or psychotic symptoms. We provided a case of a 43-years-old female patient suffering from schizophrenia with significant suicidal ideation and showed that ketamine infusions intravenously at a subanesthetic dose of 0.5mg/kg with a syringe pump infusion had a strong anti-suicidal impact. Importantly, no relevant psychotic or dissociative symptoms occurred during the duration of the augmentation treatment, resulting in prolonged remission of suicidality. This intervention with ketamine was safe and showed significant alleviation of suicidality which might inspire future studies. Bang J Psychiatry 2023;37(2): 46-48